ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN ISTRI PETANI MEMILIH BEKERJA ATAU TIDAK BEKERJA DI LUAR RUMAH TANGGA - Arianti, Nyayu Neti; Priyono, Basuki Sigit (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2005)
The aims of this research were to know the reasons of farmer’s wives behind their decision to work or not outside their family duties and to investigate the factors influenced their decision and how much their economic contribution to family income. This research took place in Peck Nearing village, Ponder Kelp sub regency, North Engulf regency. Descriptive and logic regression model was used to achieve the purposes. The research found that an economic reason that is the contributing to family income is the main reason for them to work which is indicating by 58,33 % of 68 population, utilization of leisure time is decide reason for 80,56 % population to while culture gender reason by 88,89 %. The logic model analysis showed that formal education, informal education, age, and family size influenced the farmer’s wife decision, while the husband income as farmer did not, the economic contribution to family income was 56, 94 %.